QUICK RESPONSE USING FORENSIC ENGINEERING ON STRUCTURAL BUILDING DAMAGE - Jonbi Jonbi (Jurnal Infrastruktur, 2022)
Quick response and emergency when buildings are damaged by earthquakes and other situations to determine the causes and ensure that the structure of the building can still be used safely. The additional building of one the heritage buildings in Jakarta currently being used as an office was observed to have suffered damages in the form of torsion of the beams, cracks in beams and walls, as well as the subsidence in floors. Therefore, this research was conducted to investigate these sudden and quick damages using forensic engineering through visual observations, Ultrasonic Pulse Velocity testing, Profometer, Cone Penetration Test, Ground Penetrating Radar, and structural analysis. The visual observation results showed the existence of cracks in the beams, walls, and columns as well as a maximum deformation of 94 mm, especially in the dilation area or the border between the main building and the additional building around the lobby and the floors above it. Moreover, the improper structural system caused the damage as observed with one column having an ultimate axial load of 114 tons while the surrounding columns were only 25-50% of this value. The quick response provided was observed to be the addition of steel columns, beam strengthening with FRP, and zoning of usable space in buildings. The quick response also showed the main damage was caused by the dewatering work of the office construction project near the building and this can be used by the building owner as the basis to submit a claim to the responsible party.